2004
DOI: 10.1128/aac.48.1.326-328.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parenteral Fluoroquinolone Administration on Persistence of Vancomycin-Resistant Enterococcus faecium in the Mouse Gastrointestinal Tract

Abstract: We examined the effect of subcutaneous fluoroquinolone antibiotic administration on persistence and density of vancomycin-resistant Enterococcus faecium stool colonization in mice. Levofloxacin and ciprofloxacin did not promote colonization in comparison to saline controls, whereas moxifloxacin and gatifloxacin promoted persistent overgrowth in a dose-dependent fashion.In a mouse model and in colonized patients, we have demonstrated that antibiotics with potent in vitro activity against intestinal anaerobes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 16 publications
5
101
0
1
Order By: Relevance
“…Eight out of eight mice who had received prior oral vancomycin became colonized with VRE, with counts ranging from 3.2 ϫ 10 6 to 8.3 ϫ 10 9 CFU/g of feces on D9 (48 h after VRE inoculation) ( Fig. 1), similar to the observations of Donskey et al (1). These levels of VRE fecal concentration persisted for 9 days, including 2 days after vancomycin was stopped, and then rapidly declined to reach a level of 10 3 to 10 4 CFU/g of feces on D26, which was maintained in five mice up to D80 (Fig.…”
supporting
confidence: 78%
“…Eight out of eight mice who had received prior oral vancomycin became colonized with VRE, with counts ranging from 3.2 ϫ 10 6 to 8.3 ϫ 10 9 CFU/g of feces on D9 (48 h after VRE inoculation) ( Fig. 1), similar to the observations of Donskey et al (1). These levels of VRE fecal concentration persisted for 9 days, including 2 days after vancomycin was stopped, and then rapidly declined to reach a level of 10 3 to 10 4 CFU/g of feces on D26, which was maintained in five mice up to D80 (Fig.…”
supporting
confidence: 78%
“…Although previous studies have demonstrated that antibiotic treatment can lead to increased colonization of the intestine by VRE (17,34), to our knowledge, the prevalence of VRE relative to other intestinal microbes has not been previously determined. To address this question, untreated and ampicillin-treated mice were infected with 10 8 CFUs of VRE.…”
Section: Antibiotic Effect On Vre Intestinal Colonization In Micementioning
confidence: 81%
“…Several pathogens were studied here, including E. faecium C68, a previously described VanB-type clinical VRE isolate (7). K. pneumoniae P62 is a clinical isolate that produces an SHV type extendedspectrum ␤-lactamase (ESBL).…”
Section: Methodsmentioning
confidence: 99%
“…K. pneumoniae P62 is a clinical isolate that produces an SHV type extendedspectrum ␤-lactamase (ESBL). Both organisms have been used in previous mouse model studies (7,8).Susceptibility testing. Broth dilution MICs of the test antibiotics for the test organisms were determined using standard methods for susceptibility testing of aerobic bacteria (9).…”
mentioning
confidence: 99%